Total and Structural Carotid Artery Stiffness Are Associated With Cognitive Decline and Structural Brain Abnormalities Related to Alzheimer Disease and Alzheimer Disease‐Related Dementias Pathology: The Multi‐Ethnic Study of Atherosclerosis - Williams, Jeremy R.; DeConne, Theodore M.; Pewowaruk, Ryan; Korcarz, Claudia; Tanley, Jordan; Carlsson, Cynthia; Heckbert, Susan R.; Habes, Mohamad; Nasrallah, Ilya; Lockhart, Samuel N.; Luchsinger, José A.; Ding, Jingzhong; et al. (Journal of the American Heart Association, 2025)
Arterial stiffness is associated with pathological changes underlying Alzheimer disease and related dementias. Total pulse wave velocity can be subdivided into 2 main mechanisms: structural arterial stiffness (S-PWV) due to intrinsic remodeling of the artery wall and load-dependent arterial stiffness due to increased blood pressure. In this prospective cohort study, MESA (Multi-Ethnic Study of Atherosclerosis) participants completed B-mode carotid ultrasounds from which carotid total pulse wave velocity was calculated. S-PWV was calculated by adjusting pulse wave velocity to 120/80 mmHg using a nonlinear pressure-diameter relationship, and load-dependent arterial stiffness was derived by subtracting S-PWV from total pulse wave velocity. Participants had repeated cognitive assessments with the Cognitive Abilities Screening Instrument, Digit Symbol Coding, and Digit Span combined into a global cognitive composite (N=2489). Brain magnetic resonance imaging was used to generate total gray matter volume (N=906), white matter hyperintensity volume (N=896), and total white matter fractional anisotropy (N=810). Multivariable linear fixed and mixed effects regression models related standardized pulse wave velocity components to neuroimaging and cognitive decline parameters, respectively. Greater S-PWV was associated with greater longitudinal cognitive decline in global cognitive composite score (β=-0.05, =0.002) and subtests, whereas greater load-dependent arterial stiffness was not associated with longitudinal cognitive decline. Greater S-PWV was associated with lower gray matter volume (β=-3183.4, =0.013) and higher log white matter hyperintensity volume (β=0.20, <0.001), whereas load-dependent arterial stiffness was associated with lower total white matter fractional anisotropy (β=-0.004, ≤0.001). Higher structural stiffness of the carotid artery is associated with cognitive decline, whereas both structural and load-dependent stiffness are associated with brain structural abnormalities common in Alzheimer disease-related dementias.